Modification of Sago Starch Through Lintnerization and Its Impact on Biodegradable Straw Properties - Dwi Ardiana Setyawardhani; Sinta Kristiana Putri; Putri Fadilla Nisa; Fikriyyah Nur Hidayati; Hananda Christy Sutoyo (Equilibrium Journal of Chemical Engineering, 2026)
The increasing environmental burden caused by plastic waste necessitates the exploration of sustainable alternatives such as starch-based biodegradable products. Sago starch, a renewable polysaccharide offers potential for such applications. However, its inherent limitations such as poor thermal stability and water resistance restrict its use in biodegradable product. This study investigates the effect of lintnerization, a mild acid hydrolysis process on the physicochemical properties of sago starch and evaluates its performance in biodegradable straw production. Sago starch was modified through a 120-hour lintnerization process using 2.2 N HCl, followed by washing and drying to obtain crystalline starch. The resulting starch was characterized by XRD and SEM, and its application in straws was assessed via yield, organoleptic tests, tensile strength, water resistance, and biodegradability. The yield of crystalline starch reached 99.89%, with organoleptic scores indicating good visual and textural quality. XRD analysis revealed an increase in crystallinity from 33.32% to 49.98%, while SEM confirmed significant granule degradation. Incorporating crystalline starch improved straw water resistance up to 83.65% and tensile strength up to 7.05 MPa fulfilling industry standards. However, the biodegradability test results were unreliable due to uncontrolled external factors. These findings demonstrate that lintnerization enhances starch performance for biodegradable applications.